Elevated levels of plasma transforming growth factor-β1 in idiopathic and heritable pulmonary arterial hypertension. (1st November 2016) - Yan, Yi; Wang, Xiao-Jian; Li, Su-Qi; Yang, Shu-Hui; Lv, Zi-Chao; Wang, Li-Ting; He, Yang-Yang; Jiang, Xin; Wang, Yong; Jing, Zhi-Cheng
Abstract: Background: Aberrant transforming growth factor (TGF)-β signaling is involved in the pathogenesis of pulmonary arterial hypertension (PAH). We aimed to investigate the predictive value of the upstream ligand of TGF-β signaling (TGF-β1) on long-term mortality and the clinical characteristics of patients with idiopathic pulmonary arterial hypertension (IPAH) and heritable PAH (HPAH). Methods and results: Plasma TGF-β1 levels were measured in 151 IPAH and 65 HPAH patients retrospectively enrolled between January 2008 and March 2013, and compared to 61 healthy subjects. Data for mortality over time were obtained from hospital databases and from telephone follow-ups. The main outcome was all-cause death. Plasma TGF-β1 was significantly higher in IPAH/HPAH patients compared to control subjects (4.74 vs. 2.61 ng/mL, respectively; P  < 0.001). Mean follow-up time was 3.4 ± 1.8 years, during which 86 patients died. ROC curves were utilized to determine TGF-β1 cutoff values. Compared to patients with TGF-β1 of < 3.74 ng/mL, heart function was significantly impaired (percentage of patients with WHO functional class III/IV, 51.4% vs. 65.5%, P  = 0.043) and mortality risk was elevated ( P  = 0.009) for patients with TGF-β1 > 3.74 ng/mL. However, the difference in mortality rate between patients with higher and lower TGF-β1 levels was only statistically significant for female patients ( P  = 0.004), despite a similar trend for male patients. Multivariate analyses revealed that TGF-β1 (HR after log transformation base of 10: 2.623; 95%CI: 1.228–5.603; P  = 0.013) emerged as the independent predictor for all-cause mortality. Conclusion: High circulating levels of TGF-β1 were an independent predictor of a poor outcome for IPAH/HPAH patients.